Anomalously Slow Conformational Change Dynamics of Polar Groups Anchored to Hydrophobic Surfaces in Aqueous Media. Issue 20 (14th September 2020) - Fu, Tengfei; Xing, Hao; Silver, Eric S.; Itoh, Yoshimitsu; Chen, Shuo; Masuda, Takuya; Uosaki, Kohei; Huang, Feihe; Aida, Takuzo
Abstract: Water molecules within a thin hydration layer, spontaneously generated on hydrophobic protein surfaces, are reported to form a poorly dynamic network structure. However, how such a water network affects the conformational change dynamics of polar groups has never been explored, although such polar groups play a critical role in protein‐protein and protein‐ligand interactions. In the present work, we utilized as model protein surfaces a series of self‐assembled monolayers (SAMs) appended with polar (Fmoc) or ionic (FITC) fluorescent head groups that were tethered via a 1.5‐nm‐long flexible oligoether chain to a hydrophobic silicon wafer surface, which was densely covered with paraffinic chains. We found that, not only in deionized water but also in aqueous buffer, these oligoether‐appended head groups at ambient temperatures both displayed an anomalously slow conformational change, which required ∼10 h to reach a thermodynamically equilibrated state. We suppose that these behaviors reflect the poorly dynamic and low‐permittivity natures of the thin hydration layer. Abstract : Self‐assembled monolayers featuring polar functional groups dispersed on a hydrophobic surface exhibited an anomalously slow conformational change dynamics, which lasted for a period of ∼10 h to reach a thermodynamic equilibrium at ambient temperatures. Considering that such a surface structure is akin to a protein surface, where polar functional groups located within hydrophobic domains play a critical role in protein‐protein and protein‐ligand interactions, this finding would provide an interesting insight into biomolecular recognition events.